Speolabeo hokhanhi, a new cavefish from Central Vietnam (Teleostei: Cyprinidae) - Tao, Nguyen Dinh; Cao, Liang; Deng, Shuqing; Zhang, E (Zootaxa, 2018)
Speolabeo hokhanhi, new species, is here described from Hang Va Cave in Phong Nha-Ke Bang National Park (Son River basin) in Central Vietnam. It can be distinguished from S. musaei by having no papillae on the lower lip, no hump immediately behind the head, a duckbilled snout, a shorter caudal peduncle (length 16.8–18.6% SL), and the pelvic fin inserted closer to the snout tip than to the caudal-fin base.